Education and Social Inclusion Based on the Example of People with Disabilities - Szluz, Beata (Havlíčkův Brod: Tobiáš, 2013)
In this article an attempt was made to find a reply to the question: what is the role of education in the prevention and elimination of social exclusion? The purpose of this consideration is to present the barriers faced by people with disabilities, the context of their exclusion, as well as social integration. It presents the chosen methods of working with individual with disabilities, as promoting innovation in education optimizes the chances for the full participation of disabled persons in social life.

Příspěvek se pokouší poskytnout odpověď na otázku, jakou roli hraje vzdělání v prevenci a eliminaci sociálního vyloučení. Účelem těchto úvah je upozornit na překážky, kterým lidé s postižením čelí, stejně jako na kontext jejich vyloučení a zároveň na sociální integraci. V textu jsou prezentovány vybrané metody práce s jedinci se zdravotním postižením. Podpora inovací ve vzdělávání optimalizuje šance na plnou účast osob se zdravotním postižením na společenském životě.
Vzdělávání a sociální inkluze na příkladu lidí se zdravotním postižením
Inkluzivní trendy ve speciální pedagogice Editoři: Miroslav Meier, Jan Jihlavec, Ilona Pešatová, Bohumil Stejskal
Keywords: disabilities; postižení; social problem; social exclusion; social inclusion; education; sociální problém; sociální vyloučení; sociální začlenění; vzdělání